An investigation of maternal food intake and maternal food talk as predictors of child food intake. (1st August 2018) - DeJesus, Jasmine M.; Gelman, Susan A.; Viechnicki, Gail B.; Appugliese, Danielle P.; Miller, Alison L.; Rosenblum, Katherine L.; Lumeng, Julie C.
Abstract: Though parental modeling is thought to play a critical role in promoting children's healthy eating, little research has examined maternal food intake and maternal food talk as independent predictors of children's food intake. The present study examines maternal food talk during a structured eating protocol, in which mothers and their children had the opportunity to eat a series of familiar and unfamiliar vegetables and desserts. Several aspects of maternal talk during the protocol were coded, including overall food talk, directives, pronoun use, and questions. This study analyzed the predictors of maternal food talk and whether maternal food talk and maternal food intake predicted children's food intake during the protocol. Higher maternal body mass index (BMI) predicted lower amounts of food talk, pronoun use, and questions. Higher child BMI z-scores predicted more first person pronouns and more wh-questions within maternal food talk. Mothers of older children used fewer directives, fewer second person pronouns, and fewer yes/no questions. However, maternal food talk (overall and specific types of food talk) did not predict children's food intake. Instead, the most robust predictor of children's food intake during this protocol was the amount of food that mothers ate while sitting with their children. These findings emphasize the importance of modeling healthy eating through action and have implications for designing interventions to provide parents with more effective tools to promote their children's healthy eating.